Chronic Total Occlusion-Angioplasty with Antegrade Approach: A two-Year Experience in âModarres Hospitalâ, A Tertiary University Hospital, Tehran, Iran - Safi, Morteza; Namazi, Mohammad Hasan; Sadeghi, Hamid; Saadat, Habibollah; Vakili, Hossein; Alipour Parsa, Saeed; Khaheshi, Isa; Ataeinia, Bahar (International Journal of Cardiovascular Practice, 2016)
Introduction: New techniques for the percutaneous treatment of coronary chronic total occlusions (CTO) have had a high success rate since a few years ago, so the interest for this treatment has been increasing these days.Methods: The current observational study was performed in Modarres hospital as a tertiary referral center. All the patients with documented stable angina who had failed to response to full guideline-mediated medical therapy, referred to our hospital, were candidates for coronary angiography. Antegrade strategy was applied for all these patients. The length of the lesion, the fluoroscopy time of the CTO angioplasty, consumed contrast volume, the number of guide wires used, whether a corsair or tornus micro-catheter was used or not, and the success rate of the angioplasty were documented for further analysis.Results: A total of 47 patients with documented stable angina were finally included. The median age was 59 (45-78) and 70.2% were male. The mean length of the lesion was 34.0 Â± 1.1 .The mean fluoroscopy time and contrast volume were 57.9 Â± 3.2 minutes and 525.9 Â± 20.9 mL, respectively. In average, 2.2 guide wires were used. Corsair and tornus micro-catheters were applied in 30 (63.8%) and 5 (10.6%) of the cases, respectively. Seven complications (all including coronary dissection) occurred. In-hospital major adverse cardiac events (MACE) rate was 10.6%, all of which were non-Q wave myocardial infarction. The success rate was 85.1%. The higher number of used wires, use of corsair, and tornus micro-catheter were not significantly concordant with success rate (P-value > 0.05); in addition, longer lesion was not concordant with unsuccessfulness rate (P-value > 0.05).Conclusions: Patient selection for CTO-angioplasty should be performed more carefully. Patientsâ quality of life and risk of probable procedural complications and future cardiac events should be assessed to decide the best treatment approach. Radiation exposure, contrast consumption and fluoroscopy time are recommended to be monitored during the procedure and thresholds should be defined to enhance safety and efficacy.